Influence of different types of fertilizers on growth and physiology changes of MD2 pineapple - Abu Samah, Mohd Nor Ghani (2015)
This study prevails the influence of different types of fertilizers used in pineapple plantations in Malaysia. The studies also indicated to recommend the best performance fertilizer for pineapple crop to be used. In this study, pineapple variety chosen was MD2 from Cayenne group that have high production yield and broader aspects in terms of quality and consumer preferences. Treatments were arranged in complete block design with three replications and carried out in the open environment. This study compared the performance of different fertilizers and fertilizers combination which is NPK, Kamila, and SRI fertilizer used solely or combined in several aspects which is growth performance in height of crop, length of leaf, and width of crop, relative chlorophyll content, nutrient analysis in leaves and soil, and pH. Besides that, these were to determine which type of fertilizers used solely or combined were the best in giving positive impact to the crop performance. NPK fertilizer was a fast release fertilizer while Kamila was a controlled-release fertilizer. These two fertilizers contributed major nutrients supply to the crop which was nitrogen, phosphorus, and potassium. For SRI fertilizer, it was a foliar fertilizer functioned to improve nutrient uptake and intensified the roots. Data were analyzed by using SAS version 9.1. As controlled release fertilizer characteristic of releasing the nutrients slowly, it gave stability to the nutrient supply to the treated plants throughout the experiment compared to other treatment. Additional of chemical fertilizer (Kamila) with SRI formulation significantly shows positive improvement in the plant performance compared to the plants without SRI formulation and is recommended for the pineapple planting as it performed better on parameters measured. However, many aspects need to be considered as the experiment was conducted in open condition.